Enterovirus 71 Suppresses miR-17-92 Cluster Through Up-Regulating Methylation of the miRNA Promoter - Fu, Yuxuan; Zhang, Li; Zhang, Rui; Xu, Shijie; Wang, Huanru; Jin, Yu; Wu, Zhiwei (Frontiers in Microbiology, 2019)
Enterovirus 71 (EV71), the etiological agent of hand-foot-and-mouth disease, has become an increasing public health challenge worldwide. Accumulating evidence suggests that mammalian microRNAs (miRNAs), a class of non-coding RNAs of 18 to 24 nucleotides (nt) with important regulatory roles in cellular processes, participate in host antiviral defense and studies have suggested roles of miRNAs in EV71 replication and pathogenesis. In the current study, we reported that the expression of hsa-miR-17∼92 cluster was significantly downregulated during EV71 infection. Overexpression of hsa-miR-17∼92 inhibited, while inhibition of endogenous hsa-miR-17∼92 facilitated EV71 replication. We identified two sequences located at nt 3024 to 3038 and nt 2838 to 2862 of the EV71 (strain FY0805) genome as potential targets for hsa-miR-17-5p and miR-19a/b, respectively, which were validated by luciferase reporter assays and Western blot. Meanwhile, we identified DNA methylation as a novel mechanism of hsa-miR-17∼92 regulatory roles. The methylation of the miR-17-92 promoter was significantly increased (50%) upon EV71 infection, which appeared to be caused by the increased expression of DNMT3B but not DNMT1 and DNMT3A. Furthermore, we demonstrated that the members of miR-17-92 cluster were decreased in the sera of EV71 infected patients, suggesting the clinical implication and the potential therapeutic application of miR-17-92.